2020
DOI: 10.1111/jog.14487
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for Gynecological Practice in Japan: Japan Society of Obstetrics and Gynecology and Japan Association of Obstetricians and Gynecologists 2020 edition

Abstract: Nine years after the first edition of The Guideline for Gynecological Practice, which was jointly edited by The Japan Society of Obstetrics and Gynecology and The Japan Association of Obstetricians and Gynecologists, the 4th Revised Edition was published in 2020. The 2020 Guidelines includes 4 additional clinical questions (CQ), which brings the total to 99 CQ (12 on infectious disease, 29 on oncology and benign tumors, 29 on endocrinology and infertility and 29 on healthcare for women). Currently, a consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Both the latest JSOG guidelines and the American College of Obstetricians and Gynecologists (ACOG) guidelines indicate that IAP is most effective when administered at least 4 h before delivery. 11,28 Sakata et al reported that among 169 neonates born to mothers after IAP, all of seven neonates (4.1%) who showed GBS colonization at birth were born within 90 min of IAP administration, 29 suggesting that inappropriate IAP is less effective in preventing GBS transmission to neonates. Furthermore, the mothers of two GBS-positive cases (case #1 and 4) were tested for GBS prior to 35 weeks of GA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the latest JSOG guidelines and the American College of Obstetricians and Gynecologists (ACOG) guidelines indicate that IAP is most effective when administered at least 4 h before delivery. 11,28 Sakata et al reported that among 169 neonates born to mothers after IAP, all of seven neonates (4.1%) who showed GBS colonization at birth were born within 90 min of IAP administration, 29 suggesting that inappropriate IAP is less effective in preventing GBS transmission to neonates. Furthermore, the mothers of two GBS-positive cases (case #1 and 4) were tested for GBS prior to 35 weeks of GA.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal GBS screening and IAP conformed to the Japan Society of Obstetrics and Gynecology recommendations. 11 We reviewed the neonatal and maternal medical records of participants and extracted patient data, including maternal/neonatal characteristics known to be associated with EOD and microbiological test results.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction and augmentation of labor is one of the most common obstetrical interventions all over the world [ 1 , 2 ]. Fetal factors such as prolonged pregnancy and fetal growth restriction, and maternal factors such as hypotonic uterine dysfunction, premature rupture of membranes and preeclampsia are medically indicated [ 3 , 4 ]. However, this intervention is not free of risks, although the benefits of labor induction typically outweigh the risks.…”
Section: Introductionmentioning
confidence: 99%
“…To reveal mechanistic insight into potential brain damage due to induced labor, we established a new animal model of induced labor with high-dose oxytocin (OXT) [ 10 ]. Of the three medications recommended for labor induction or augmentation (OXT, Prostaglandin F2α and Prostaglandin E2), OXT is the most commonly used to increase uterine contractions [ 3 ]. Our previous study [ 10 ] showed induced labor with high-dose OXT in pregnant mice resulted in male offspring-specific cell death in several specific brain regions, such as the prefrontal cortex (PFC), habenular nucleus and periventricular nucleus.…”
Section: Introductionmentioning
confidence: 99%